Effect of Feeding Rumen Bypass Fat on Productive and Reproductive Performance of Buffaloes under Field Conditions - Prajapati, Dhruv C.; Patel, Dilip C.; Patel, Shaweta N; Dhami, Arjun J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to evaluate the effects of supplementation of bypass fat one month pre-parturition and three months of early lactation on milk production and reproductive performance of buffaloes. Thirty two multiparous pregnant buffaloes (2-3 lactation) were selected at farmers’ doorstep in Dahod District, Gujarat, and were divided into two equal groups, each of 16 animals, on the basis of their milk production and fat % during previous lactation. Animals in T1 group (n=16, control) were fed as per farmers’ feeding schedule, and those in T2 group were additionally supplemented with bypass fat @ 100 g/h/d during prepartum and 20 g/kg of milk yield during postpartum phase. The overall average whole milk yield (kg/head/d) of buffaloes was significantly (p
Keywords: Bypass fat; Milk composition; Milk yield; Reproductive performance; Transition buffalo